Ultrathin-shell IrCo hollow nanospheres as highly efficient electrocatalysts towards the oxygen evolution reaction in acidic media. Issue 47 (26th November 2020) - Zhu, Jinhui; Wei, Min; Meng, Qinghao; Chen, Zhenyu; Fan, Yepeng; Hasan, Syed Waqar; Zhang, Xiaoran; Lyu, Dandan; Tian, Zhi Qun; Shen, Pei Kang
Abstract : IrCo hollow nanospheres featuring a novel structure with ultrathin continuous shells are synthesized and exhibit the outstanding oxygen evolution reaction performance. Abstract : Improving the utilization of Ir electrocatalysts for the oxygen evolution reaction (OER) to significantly reduce their loading is essential for low-cost hydrogen production in proton exchange membrane water electrolysis. Herein, IrCo hollow nanospheres featuring a novel structure with ultrathin continuous shells which have only eleven atomic layers (2.26 nm) were synthesized by a facile sequential reduction route using NaBH4 as a reducing agent at room temperature. It is revealed that the key intermediate in the formation of hollow nanospheres is amorphous cobalt boride formed between Co 2+ and NaHB4 in the first reducing step. The average diameter of the IrCo nanospheres was found to be 73.71 nm with the atomic ratio of 47.1% and 52.9% for Co and Ir, respectively. The IrCo hollow nanospheres exhibit highly efficient OER activity and long-term durability with a low overpotential of 284 mV at 10 mA cm −2 (32.5 μgIr cm −2 ) and a high mass activity of 8.49 A mg −1 (5.7 times higher than that of commercial IrO2 (1.49 A mg −1 ) at 1.7 V. The performance is also proved using an overall water splitting device with the overpotential of 318 mV to achieve 10 mA cm −2 as well as a 17 mV shift at 5 mA cm −2 after 14 h. This improvement is critically attributed to the advantages of the hollow structure, ultrathin continuous shells which are oxidized into IrO x in situ and strong lattice strain effects induced by the specific hollow structure and alloying Co into Ir crystal lattices (1.6% against metallic iridium). These characteristics endow the hollow nanospheres with great potential to minimize the Ir loading dramatically for practical applications, compared to other previously reported structures like nanoparticles, nanoneedles and nanowires.